Genetic and non-genetic factors affecting lactation persistency in Jersey crossbred cows - Mandal, Ajoy; Singh, Laishram Arjun; Talokar, Amol J; Koloi, Subrata; Mandal, D K; Karunakaran, M (Indian Journal of Dairy Science, 2018)
The present study was conducted on 1290 lactational milk yield records of 378 Jersey crossbred cows maintained at Cattle Yard of Eastern Regional Station of ICAR- National Dairy Research Institute, Kalyani for a period of 36 years (1980 through 2015). In this study, the different persistency indices of animals were significantly influenced by different environmental factors like season of birth/calving, period of birth/calving and parity of dam. The animals calved in winter were most persistent than summer and rainy calvers. Though, there was no definite trend of lactation persistency of animals over the periods of calving, but cows calved during earlier years/periods had comparatively higher persistency than the cows calved in later years/periods. Cows in first parity/lactation had the highest persistency than those in other parity. The persistency values tended to decrease with advance of age (parity), until the fifth lactation. Animals having a genetic combination of (½ Jersey X ½ Red Sindhi) had much higher persistency followed by of (½ Jersey X ¼ Red Sindhi X ¼ Tharparkar) and (½ Jersey X ⅜ Red Sindhi X ⅛ Tharparkar) than animals of other genetic groups.